N-doped porous carbon nanorod and its preparation method and application

By preparing N-doped porous carbon nanorods with polypyrroles as the precursor and modifying them on a glass carbon electrode, the problems of insufficient sensitivity to detection of dopamine and poor dispersion performance of carbon nanospheres in the prior art are solved, and more efficient dopamine detection is achieved.

CN116002664BActive Publication Date: 2025-03-25TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211648279.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-03-25
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

Existing electrochemical sensors have insufficient sensitivity when detecting dopamine, and the poor dispersion performance of carbon nanosphere particles affects the detection efficiency.

Method used

By carbonizing in an argon atmosphere with uniform morphology, N-doped porous carbon nanorods with uniform size were prepared by using polypyrrole nanorods with uniform morphology as the precursor, and their dispersed liquid was applied to the surface of the glass carbon electrode to form a modified electrode to improve detection efficiency.

Benefits of technology

The N-doped porous carbon nanorod has a large specific surface area, good conductivity and dispersion properties, which significantly improves the electrochemical response to dopamine, has better detection effect and simple operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116002664B_ABST
    Figure CN116002664B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrochemical analysis and testing or clinical medicine technology, and provides an N-doped porous carbon nanorod and a preparation method and application thereof. Polypyrrole nanorods PPy with uniform morphology are used as precursors, and carbonization is carried out in an argon atmosphere to obtain nitrogen-doped porous nanocarbon rods. Dispersed droplets of N-doped carbon nanorods are applied to the surface of a glassy carbon electrode to prepare an N-doped carbon nanorod modified glassy carbon electrode, and the modified glassy carbon electrode simultaneously detects dopamine. Since the N-doped carbon nanorods have a large specific surface area, high conductivity, strong adsorption capacity and good mass transfer effect, dopamine is simultaneously detected using the N-doped carbon nanorod modified glassy carbon electrode. The detection method of the present invention has the advantages of high recovery rate, high sensitivity, simple method and accurate results.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical analysis and testing or clinical medicine technology, and provides an N-doped porous carbon nanorod and a preparation method and application thereof. N-doped porous carbon nanorods NNR with uniform size are prepared using polypyrrole nanorods with uniform morphology as precursors. The NNRs can be used as electrode modification materials to electrochemically detect dopamine in the central nervous system. Background Art

[0002] Dopamine is a brain secretion and a neurotransmitter containing catecholamines. It has the function of regulating various physiological functions of the central nervous system. It is related to human desire and feelings, and can convey messages of excitement and happiness. For example, when love occurs, dopamine is secreted, making people blush and excited; however, diseases such as Parkinson's disease, schizophrenia, attention deficit hyperactivity disorder, and pituitary tumors are caused by disorders in the dopamine system. Therefore, the study of its determination method is of great significance in clinical medical applications or the diagnosis of related diseases.

[0003] Since electrochemical sensors are used to detect hydroxyl groups, bare electrodes cannot meet the requirements of low sensitivity. Therefore, modifying the bare electrodes with modified materials can effectively reduce the surface resistance of the sensors, thereby improving the detection efficiency. This is also a popular direction for preparing electrochemical sensors in current electrochemical research.

[0004] Polypyrrole (PPy) is a new functional polymer material developed in recent years. Using PPy as a precursor to prepare nitrogen-doped carbon nanospheres can improve their non-hydrophilic properties. In recent years, people have conducted a lot of research on carbon nanoparticles, especially carbon nanospheres with a diameter of less than 100 nm, but due to their poor dispersion and easy aggregation, modification has a significant adverse effect. Summary of the invention

[0005] The present invention provides an N-doped porous carbon nanorod and a preparation method and application thereof. Since the N-doped carbon nanorod has a large specific surface area, good electrical conductivity and dispersion performance, dopamine can be measured simultaneously and quickly.

[0006] The present invention is realized by the following technical scheme: an N-doped porous carbon nanorod is prepared by carbonizing a polypyrrole nanorod PPy with uniform morphology as a precursor in an argon atmosphere to obtain a nitrogen-doped porous nanocarbon rod.

[0007] The method for preparing the N-doped porous carbon nanorods comprises the following specific steps:

[0008] (1) Preparation of conductive polymer PPy nanorod powder: 80-85 μL of pyrrole monomer Py was dissolved in 1 mL of isopropanol and stirred for 20 min to obtain a uniform solution A; 0.274 g of ammonium persulfate APS, 2 mL of water and 0.003 g-0.024 g of TMCPP were then mixed to obtain a solution B; the two solutions were cooled to 4 °C and then taken out and quickly mixed; Py was polymerized for 6 h, and then the precipitate was filtered and washed with deionized water and ethanol to remove the unreacted oxidant and monomer, and finally dried at 60 °C for 12 h to obtain a conductive polymer PPy nanorod powder;

[0009] (2) Preparation of N-doped porous carbon nanorods: The conductive polymer PPy nanorod powder prepared in step (1) is carbonized in a vacuum tube furnace; the temperature is increased to 700-900°C at a heating rate of 10°C / min under an argon atmosphere and kept at this temperature for 2-5 h to obtain N-doped porous carbon nanorods NPC.

[0010] The present invention also provides an application of the N-doped porous carbon nanorods in detecting dopamine, wherein dispersed droplets of the N-doped carbon nanorods are applied on the surface of a glassy carbon electrode to obtain a glassy carbon electrode modified with the N-doped carbon nanorods, and then the modified glassy carbon electrode is used to detect dopamine; the specific steps are as follows:

[0011] (1) N-doped carbon nanorod modified glassy carbon electrode NNR / GCE: The glassy carbon electrode GCE was polished with 1.0, 0.3 and 0.05 μM α-Al2O3 powder solution in sequence, and then ultrasonically cleaned with deionized water, HNO3 with a mass ratio of 1:1 and acetone for 3 min respectively to obtain a clean glassy carbon electrode; N-doped porous carbon nanorods NPC were dispersed in high-purity water and ultrasonically treated to obtain a NNR dispersion with a concentration of 2.0 mg / mL. 5.0 μL of the NNR dispersion was dropwise coated on the cleaned GCE surface and dried under an infrared lamp to obtain the electrode NNR / GCE;

[0012] (2) Detection of dopamine using NNR / GCE: NNR / GCE is used as the working electrode, saturated calomel electrode is used as the reference electrode, and platinum wire electrode is used as the auxiliary electrode to form a three-electrode system;

[0013] The three-electrode system was first placed in a 20×10 -6 mol·L -1 Dopamine was placed in a PBS buffer solution with a pH of 7.0 and allowed to stand for 10 seconds. Cyclic voltammetry was used to scan the potential range from 0 V to 1.2 V and record the cyclic voltammetry curve to detect the electrochemical behavior of dopamine on the NPC / GCE surface.

[0014] Differential pulse voltammetry was used to scan different concentrations of dopamine in the potential range of 0.0 V to 1.2 V. The parameters of the differential pulse voltammetry method were set as follows: the potential increment was 4 mV; the amplitude was 25 mV; the differential pulse voltammetry curve was recorded, and the oxidation peak current value of dopamine was read out;

[0015] The obtained data were statistically analyzed with the concentration of dopamine as the horizontal axis and the peak current value as the vertical axis. - 11 mol·L -1 ~2.5×10 -5 mol·L -1 The standard curve was drawn within the range, and the detection limit was 9.0×10 -12 mol·L -1 The linear regression equation for dopamine is I(μA)=0.034×C(10 -8 M)+0.25 (R 2 =0.99); using the obtained linear regression equation to determine the concentration of dopamine in the actual sample;

[0016] (3) Actual sample testing: Place the sample in a volumetric flask and dilute to volume with PBS buffer solution at pH 7.0; test the sample solution using differential pulse voltammetry to obtain the oxidation peak current value of dopamine in the test solution; substitute the obtained current value into the linear regression equation corresponding to the obtained dopamine to calculate the concentration of dopamine in the sample to be tested.

[0017] Based on previous research, the present invention prepared highly dispersed polypyrrole nanorods, and used them as precursors to prepare N-doped porous carbon nanorods with good dispersion. The carbon nanorods were used to construct an electrochemical sensor for dopamine detection.

[0018] The N-doped carbon nanorods synthesized in the present invention have the characteristics of uniform nanometer size and uniform dispersion. This structure enables the N-doped carbon nanorods to have not only a large specific surface area but also good conductivity and dispersibility when used as electrode materials. The prepared electrode material significantly improves the electrochemical response to dopamine. Compared with the existing electrochemical technology, this method has better detection effect, simple operation, time saving, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a SEM image of the N-doped carbon nanorods of the present invention;

[0020] Figure 2 The specific surface area diagram of polypyrrole and N-doped carbon nanorods:

[0021] Figure 3 Impedance diagram of polypyrrole and N-doped carbon nanorods:

[0022] Figure 4 Comparative cyclic voltammograms of bare GCE, polypyrrole hydrogel modified GCE, traditional polypyrrole carbonized material modified GCE and NNR modified GCE for detecting dopamine; the polypyrrole hydrogel in the figure is a polypyrrole hydrogel prepared by the method of the present invention, and the traditional polypyrrole carbonized material is a precursor without adding a crosslinking agent during the preparation;

[0023] Figure 5 It is a differential pulse voltammogram of dopamine with different concentrations on the NNR / GCE electrode in the present invention and a linear relationship diagram with the dopamine concentration as the abscissa and the peak current value as the ordinate. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.

[0026] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.

[0027] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.

[0028] Example 1: A N-doped porous carbon nanorod, using polypyrrole nanorods PPy with uniform morphology as a precursor, carbonizing in an argon atmosphere to obtain a nitrogen-doped porous nanocarbon rod.

[0029] The specific preparation method is:

[0030] (1) Preparation of conductive polymer PPy nanorod powder: About 80-85 μL of pyrrole monomer Py was dissolved in 1 mL of isopropanol and stirred on a magnetic stirrer for 20 min to obtain a uniform solution A. Then, 0.274 g of ammonium persulfate (APS), 2 mL of water (H2O) and 0.003 g-0.024 g of TMCPP were mixed to obtain a solution B. The two solutions were then placed in a refrigerator and cooled to 4 °C, then taken out and quickly mixed to obtain a conductive polymer PPy nanorod powder. Py was polymerized for 6 h, and then the precipitate was filtered and washed with deionized water and ethanol to remove the unreacted oxidant and monomer. Finally, it was dried at 60 °C for 12 h to obtain a conductive polymer PPy nanorod powder.

[0031] (2) Preparation of N-doped porous carbon nanorods: Weigh the prepared conductive polymer PPy nanorod powder and carbonize it in a vacuum tube furnace; in an argon atmosphere, heat the temperature to 700~900℃ at a rate of 10℃ / min and keep it at this temperature for 2~5 h to obtain N-doped carbon nanorods.

[0032] Figure 1 The SEM image of the prepared N-doped carbon nanorods is Figure 1 It is obvious that the N-doped carbon nanorods prepared by the preparation method of the present invention have a thickness of about 20 nanometers and a length of about 500 nanometers or more, and have no obvious aggregation phenomenon, indicating that the dispersion is relatively uniform.

[0033] Figure 2 The specific surface area of ​​polypyrrole and carbon nanorods is shown in Figure 1. The red line in the figure has a larger adsorption capacity in the low pressure area, indicating that it has a microporous structure and a specific surface area of ​​418 cm 3 / g, which is significantly larger than the black line with a specific surface area of ​​59. Therefore, the adsorption capacity is also enhanced with the increase of specific surface area, which accelerates the adsorption of the measured sample.

[0034] Figure 3 The impedance diagram of polypyrrole and carbon nanorods. The diameter of the semicircle reflects the size of the charge transfer resistance. The smaller the semicircle, the better the electrical activity of the electrode and the greater the conductivity. It can be seen from the figure that the diameter of the semicircle of the carbon nanorod is much smaller than that of polypyrrole, proving that the conductivity of the prepared N-doped carbon nanorods has been significantly improved.

[0035] In summary, the method of the present invention is beneficial to the mass transfer effect of carbon nanorods.

[0036] N-doped porous carbon nanorods modified glassy carbon electrode to obtain NNR / GCE electrode: The glassy carbon electrode (GCE) was polished on suede with 1.0, 0.3 and 0.05 μM α-Al2O3 powder solution, and then cleaned with deionized water, HNO3 with a mass ratio of 1:1 and acetone for 3 minutes to obtain a clean glassy carbon electrode. 4.0 mg NNR was dispersed in 2.0 mL high-purity water and ultrasonicated for 30 minutes to obtain a NNR dispersion with a concentration of 2.0 mg / mL. Next, 5.0 μL of NNR dispersion was dropped on the cleaned GCE surface with a syringe with a range of 5.0 μL and dried under an infrared lamp to obtain an NNR / GCE electrode.

[0037] (3) Using N-doped carbon nanorods to modify glassy carbon electrodes to detect dopamine in solution: NNR / GCE was used as the working electrode, saturated calomel electrode was used as the reference electrode, and platinum wire electrode was used as the auxiliary electrode to form a three-electrode system;

[0038] The three-electrode system was first placed in a 20×10 -6 mol·L -1 Dopamine was placed in a PBS buffer solution with a pH of 7.0 and allowed to stand for 10 seconds. Cyclic voltammetry was then used to scan in the potential range of 0.0 V to 1.2 V, and the cyclic voltammetry curve was recorded to study the electrochemical behavior of dopamine on the NNR / GCE surface.

[0039] Comparative cyclic voltammograms of bare GCE, polypyrrole hydrogel modified GCE, traditional polypyrrole carbonized material modified GCE and NNR modified GCE for detection of dopamine Figure 4 As shown, Figure 4 It can be seen that compared with bare GCE and polypyrrole precursor modified glassy carbon electrode, as well as traditional carbonized polypyrrole material modified GCE, the oxidation peak current of dopamine on the NNR / GCE electrode was significantly enhanced.

[0040] Differential pulse voltammetry was further used to scan different concentrations of dopamine in the potential range of 0.0 V to 1.2 V. The parameters of the differential pulse voltammetry were set as follows: potential increment was 4 mV; amplitude was 25 mV; the electrochemical workstation was Shanghai Chenhua CHI 760E workstation. The differential pulse voltammetry curve was recorded (see Appendix). Figure 5 ), and read out the peak current value of dopamine oxidation; the obtained data were statistically analyzed with the concentration of dopamine as the horizontal axis and the peak current value as the vertical axis, at 1.0×10 -11 mol·L -1 ~2.5×10 -5 mol·L -1 Draw the respective standard curves within the range (see Appendix Figure 5 A, the detection limit of the sensor for dopamine is 9.0×10-12 mol·L -1 The linear regression equations for dopamine were calculated to be I(μA)=0.034×C(10 -8 M)+0.25 (R 2 =0.99), this equation can be used to determine the concentration of dopamine in actual samples.

[0041] (4) Actual sample detection: The established dopamine method is applied to the determination of actual samples. Urine is used as the actual sample to detect dopamine. The analytical technology of this method does not require special treatment. A certain amount of urine is taken with a pipette and added to a certain amount of prepared PBS buffer solution. A certain amount of urine is placed in a 100mL volumetric flask and the volume is made up to 100mL with a PBS buffer solution of pH 7.0; the sample solution to be tested is tested according to the same electrochemical test method as step (3). The experiment was not detected after scanning and testing. It is speculated that the dopamine concentration in the actual sample is lower than the detection limit of this sensor. The actual sample is spiked, then scanned and tested, and the experiment is repeated. The analysis of each sample is repeated three times, the average value is taken, the peak current value is recorded, and the obtained current value is substituted into the linear regression equation obtained by step (3) for calculation to obtain the concentration of dopamine in the sample to be tested. The results of the spiked test of 1mL of the actual sample are shown in Table 1. Obviously, the sensor shows a high recovery rate.

[0042] In addition, common components in urine include water, urea, sodium ions, chloride ions, hepatic anhydride, etc. However, from our actual detection of dopamine concentration, the recovery rate is very high, indicating that this electrode is not affected by other ions or impurities in urine during detection.

[0043] Table 1 Detection results of dopamine in actual samples

[0044]

[0045] Based on the above test results, it can be seen that the method of the present invention can detect dopamine quickly and show a high recovery rate. The method has a wide linear range for dopamine detection, high sensitivity and simple operation.

[0046] In summary, the present invention uses polypyrrole nanorods as precursors, carbonizes to prepare N-doped carbon nanorods, and applies dispersed droplets of N-doped carbon nanorods on the surface of a glassy carbon electrode to prepare a modified glassy carbon electrode. Since the N-doped carbon nanorods have a large specific surface area, high conductivity, strong adsorption capacity and good dispersibility, the experiment uses the polypyrrole nanorod modified glassy carbon electrode to carry out spiked detection of dopamine, which shows that the detection method of the present invention has the advantages of high recovery rate, high sensitivity, simple method and accurate results.

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An N-doped porous carbon nanorod, characterized in that: Using polypyrrole nanorods PPy with uniform morphology as a precursor, carbonization was carried out in an argon atmosphere to obtain nitrogen-doped porous nanocarbon rods. The specific steps of the preparation method are as follows: (1) Preparation of conductive polymer PPy nanorod powder: 80-85 μL of pyrrole monomer Py was dissolved in 1 mL of isopropanol and stirred for 20 min to obtain a uniform solution A. Then, 0.274 g of ammonium persulfate APS, 2 mL of water and 0.003 g-0.024 g of tris(1-chloro-2-propyl) phosphate (TMCPP) were mixed to obtain a solution B. The two solutions were cooled to 4 °C and then taken out and quickly mixed. Py was polymerized for 6 h, and then the precipitate was filtered and washed with deionized water and ethanol to remove the unreacted oxidant and monomer. Finally, it was dried at 60 °C for 12 h to obtain a conductive polymer PPy nanorod powder. (2) Preparation of N-doped porous carbon nanorods: The conductive polymer PPy nanorod powder prepared in step (1) is carbonized in a vacuum tube furnace; the temperature is increased to 700-900°C at a heating rate of 10°C / min under an argon atmosphere and kept at this temperature for 2-5 h to obtain N-doped porous carbon nanorods.

2. The use of the N-doped porous carbon nanorods according to claim 1 in detecting dopamine, characterized in that: The dispersed droplets of N-doped porous carbon nanorods are coated on the surface of a glassy carbon electrode to obtain a glassy carbon electrode modified with N-doped porous carbon nanorods, and then the modified glassy carbon electrode is used to detect dopamine; the specific steps are as follows: (1) N-doped porous carbon nanorods modified glassy carbon electrode NNR / GCE: The glassy carbon electrode GCE was polished with 1.0, 0.3 and 0.05 μM α-Al2O3 powder solution in sequence, and then ultrasonically cleaned with deionized water, HNO3 with a mass ratio of 1:1 and acetone for 3 min to obtain a clean glassy carbon electrode; N-doped porous carbon nanorods were dispersed in high-purity water and ultrasonically treated to obtain a NNR dispersion with a concentration of 2.0 mg / mL. 5.0 μL of the NNR dispersion was dropwise coated on the cleaned GCE surface and dried under an infrared lamp to obtain the electrode NNR / GCE; (2) Detection of dopamine using NNR / GCE: NNR / GCE is used as the working electrode, saturated calomel electrode is used as the reference electrode, and platinum wire electrode is used as the auxiliary electrode to form a three-electrode system; The three-electrode system was first placed in a 20×10 -6 mol·L -1 Dopamine was placed in a PBS buffer solution with a pH of 7.0 and allowed to stand for 10 seconds. Cyclic voltammetry was used to scan the potential range from 0 V to 1.2 V and record the cyclic voltammetry curve to detect the electrochemical behavior of dopamine on the NNR / GCE surface. Differential pulse voltammetry was used to scan different concentrations of dopamine in the potential range of 0.0 V to 1.2 V. The parameters of the differential pulse voltammetry method were set as follows: the potential increment was 4 mV; the amplitude was 25 mV; the differential pulse voltammetry curve was recorded, and the oxidation peak current value of dopamine was read out; The obtained data were statistically analyzed with the concentration of dopamine as the horizontal axis and the peak current value as the vertical axis. -11 mol·L -1 ~2.5×10 -5 mol·L -1 The standard curve was drawn within the range, and the detection limit was 9.0×10 -12 mol·L -1 The linear regression equation for dopamine is I(μA)=0.034×C(10 -8 M)+0.25 (R 2 =0.99); using the obtained linear regression equation to determine the concentration of dopamine in the actual sample; (3) Actual sample testing: Place the sample in a volumetric flask and dilute to volume with PBS buffer solution at pH 7.0; The sample solution to be tested is tested according to differential pulse voltammetry to obtain the oxidation peak current value of dopamine in the solution to be tested, and the obtained current value is substituted into the linear regression equation corresponding to the obtained dopamine to calculate and obtain the concentration of dopamine in the sample to be tested.